Dubbing as a Pedagogical Tool: An Experimental Study on Eleventh-Grade Students at SMAN 8 Samarinda - Arbain, Arbain; Rohman, Abdul; Sonia (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This study was conducted to determine the efficacy of the dubbing method on the speaking ability of eleventh-grade SMAN 8 SAMARINDA students. This research is related to the findings of previous studies, which continue to indicate that many students lack adequate speaking skills. This study employs experimental research to determine whether the dubbing method is effective or ineffective for teaching students how to communicate. The study was conducted six times, once during each of the pre- and post-tests and four times during the experiment. The obtained data is based on the pre- and post-test scores of the students. The author concludes, based on the research conducted, that the use of the dubbing method in learning is effective in enhancing students' speaking skills, as indicated by their test scores. Furthermore, the calculation of the paired sample t-test reveals a significant effect, as indicated by the sig value. 0.01 0.05, therefore Ho is rejected, so it can be inferred that the dubbing method is effective on the speaking ability of SMA Negeri 8 Samarinda eleventh graders.